2011
DOI: 10.1093/tropej/fmr020
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Dengue Shock Syndrome in Children

Abstract: This retrospective hospital-based study was conducted to evaluate the various risk factors associated with dengue shock syndrome (DSS) in patients (≤18 years of age) of dengue hemorrhagic fever (DHF). Medical records of these 483 patients with DHF (IgM serology positive) were analyzed with reference to shock for various clinical and biochemical parameters. Of the 483 children, 405 were categorized in DHF group (grade I, 282 children; grade II, 123 children) and 78 in DSS group (grade III, 59 children; grade IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
9
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 13 publications
6
46
9
8
Order By: Relevance
“…23,24 In various studies thrombocytopenia, bleeding episodes and neurological complications were found to have a significant association with severity of dengue, similar to that of our study. 25,26 Hepatomegaly was found to have a significant association with severity in a study by Sahana et al 13 Splenomegaly was seen more in non survivors than survivors in a study by Reddy BK et al, we however did not notice such an association in our study. 27 Many studies proposed hemo-concentration as a prognostic factor for the severity of dengue infection.…”
Section: Discussioncontrasting
confidence: 57%
“…23,24 In various studies thrombocytopenia, bleeding episodes and neurological complications were found to have a significant association with severity of dengue, similar to that of our study. 25,26 Hepatomegaly was found to have a significant association with severity in a study by Sahana et al 13 Splenomegaly was seen more in non survivors than survivors in a study by Reddy BK et al, we however did not notice such an association in our study. 27 Many studies proposed hemo-concentration as a prognostic factor for the severity of dengue infection.…”
Section: Discussioncontrasting
confidence: 57%
“…In this proposed model of T1 and T2 for predicting severe dengue, clinician may use it on the first day or second day to triage the patient for admission or to followup the patient vigilantly if they are tested positive in the models (above the proposed P cut-offs). Ideally, prediction should be done before the critical phase when complication develops [3,[11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…9 Adanya edema palpebra, efusi pleura atau ascites akibat dari kebocoran plasma juga merupakan faktor risiko penting pada DBD dan SSD. 10 Muntah termasuk tanda bahaya penting dalam memprediksi risiko terjadinya dengue berat, tetapi tidak ditemukan dalam penelitian kami. Hal tersebut mungkin dikarenakan belum dilakukan pencatatan data rekam medis secara lengkap sebelumnya sehingga menjadi keterbatasan dalam penelitian ini.…”
Section: Pembahasanunclassified
“…Penelitian kami dan sebelumnya mendukung perdarahan gastrointestinal yang merupakan faktor prognostik penting. 10 Hal tersebut berhubungan dengan penurunan jumlah trombosit pada infeksi dengue berat. Anak dengan SSD yang mengalami perdarahan mayor mempunyai prognosis meninggal delapan kali lebih besar atau 88% lebih tinggi dibandingkan anak dengan SSD yang tidak mengalami perdarahan mayor.…”
Section: Pembahasanunclassified
See 1 more Smart Citation